Reducing Flood Risk in Changing Environments: Optimal Location and Sizing of Stormwater Tanks Considering Climate Change - Saldarriaga, Juan; Salcedo, Camilo; Solarte, Laura; Pulgarín, Laura; Rivera, Maria Laura; Camacho, Mariana; Iglesias-Rey, Pedro L.; Martínez-Solano, Francisco Javier; Cunha, Maria (Water (Basel), 2020)
In recent years, there has been an increase in the frequency of urban floods as a result of three determinant factors: the reduction in systems’ capacity due to aging, a changing environment that has resulted in alterations in the hydrological cycle, and the reduction of the permeability of watersheds due to urban growth. Due to this, a question that every urban area must answer is: Are we ready to face these new challenges? The renovation of all the pipes that compose the drainage system is not a feasible solution, and, therefore, the use of new solutions is an increasing trend, leading to a new operational paradigm where water is stored in the system and released at a controlled rate. Hence, technologies, such as stormwater tanks, are being implemented in different cities. This research sought to understand how Climate Change would affect future precipitation, and based on the results, applied two different approaches to determine the optimal location and sizing of storage units, through the application of the Simulated Annealing and Pseudo-Genetic Algorithms. In this process, a strong component of computational modeling was applied in order to allow the optimization algorithms to efficiently reach near-optimal solutions. These approaches were tested in two stormwater networks at Bogotá, Colombia, considering three different rainfall scenarios.